High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Liu, Feng-Qi; Qu, Qing-Yuan; Lei, Ying; Chen, Qi; Chen, Yu-Xiu; Li, Meng-Lin; Sun, Xue-Yan; Wu, Ye-Jun; Huang, Qiu-Sha; Fu, Hai-Xia; Kong, Yuan; Li, Yue-Ying; et al. (Science China. Life sciences, 2024)
To investigate the role of co-stimulatory and co-inhibitory molecules on immune tolerance in immune thrombocytopenia (ITP), this study mapped the immune cell heterogeneity in the bone marrow of ITP at the single-cell level using Cytometry by Time of Flight (CyTOF). Thirty-six patients with ITP and nine healthy volunteers were enrolled in the study. As soluble immunomodulatory molecules, more sCD25 and sGalectin-9 were detected in ITP patients. On the cell surface, co-stimulatory molecules like ICOS and HVEM were observed to be upregulated in mainly central memory and effector T cells. In contrast, co-inhibitory molecules such as CTLA-4 were significantly reduced in Th1 and Th17 cell subsets. Taking a platelet count of 30×10 9 L −1 as the cutoff value, ITP patients with high and low platelet counts showed different T cell immune profiles. Antigen-presenting cells such as monocytes and B cells may regulate the activation of T cells through CTLA-4/CD86 and HVEM/BTLA interactions, respectively, and participate in the pathogenesis of ITP. In conclusion, the proteomic and soluble molecular profiles brought insight into the interaction and modulation of immune cells in the bone marrow of ITP. They may offer novel targets to develop personalized immunotherapies.